Sukuk Hijau Sebagai Instrumen Investasi Syariah Berkelanjutan di Indonesia: Analisis Peluang, Tantangan, dan Strategi Pengembangan - Nanda Mar'atus; Ismatul Khayati (UIN AM. Sangadji Ambon, 2025)
The development of green sukuk as an environmentally friendly sharia investment product is increasingly relevant amidst increasing global attention to climate change and sustainability. Green sukuk is a sharia-compliant financing instrument intended to support projects that contribute to environmental conservation, such as green infrastructure, waste management and renewable energy. The aim of this research is to analyze the concept, urgency and potential of green sukuk in the Islamic financial market, placing special emphasis on the opportunities and challenges faced in developing this instrument in Indonesia. Global case studies show that green sukuk have great potential to attract investors who care about the environment while complying with sharia financial principles. However, challenges such as lack of investor awareness, regulatory barriers and the need for clear standards remain major obstacles. Through in-depth analysis, this research provides strategic recommendations for the government, financial institutions and other stakeholders to strengthen the development of green sukuk as part of sustainable financing solutions in Indonesia. With this, green sukuk can become an important instrument that is not only economically profitable but also contributes positively to the environment and sustainable development in Indonesia.